3rd International Conference on Fuel Cell Science, Engineering and Technology 2005
DOI: 10.1115/fuelcell2005-74010
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Flow Field Combination Design on Direct Methanol Fuel Cell Performance

Abstract: The flow-field design of Direct Methanol Fuel Cells (DMFCs) is an important subject about the DMFCs performance. Flow-fields play an important role on ability to transport fuel and drive out the products (H2O, CO2). In general, most of fuel cells utilize the same structure of flow-field for both anode and cathode. The popular flow-fields used for DMFCs are parallel and grid designs. Nevertheless, the characteristics of reactants and products are entirely different in anode and cathode of DMFCs. Therefore; the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Another advantage of the serpentine flow field is that the pressure difference between two adjacent channels is larger, creating stronger under-rib convection and enhancing the removal of liquid water accumulated in the cathode DL under channel ribs. Therefore, it is generally agreed that the serpentine flow field shows the better liquid water removal ability and more stable performance [53,55,120]. The utilization of under-rib convection to mitigate the cathode flooding has also been embodied in other types of flow field, such as the interdigitated flow field [121] and the modified serpentine flow field [51].…”
Section: Effect Of the Cathode Flow Fieldmentioning
confidence: 98%
See 3 more Smart Citations
“…Another advantage of the serpentine flow field is that the pressure difference between two adjacent channels is larger, creating stronger under-rib convection and enhancing the removal of liquid water accumulated in the cathode DL under channel ribs. Therefore, it is generally agreed that the serpentine flow field shows the better liquid water removal ability and more stable performance [53,55,120]. The utilization of under-rib convection to mitigate the cathode flooding has also been embodied in other types of flow field, such as the interdigitated flow field [121] and the modified serpentine flow field [51].…”
Section: Effect Of the Cathode Flow Fieldmentioning
confidence: 98%
“…Particular attention needs to be paid to the design of the flow field such that liquid water accumulated in the cathode DL under the flow channel ribs can be effectively removed [51]. Previous visual studies showed that in both the parallel and the spot flow field, the accumulated liquid water could clog part of the flow channels, reducing the total reactive area and lowering the cell performance [53,55,120]. On the contrary, it was found that the serpentine flow field could more effectively transport liquid water out of the cell.…”
Section: Effect Of the Cathode Flow Fieldmentioning
confidence: 99%
See 2 more Smart Citations